Biopsychosocial approach to understanding determinants of depression among men who have sex with men living with HIV: a systematic review - Mohamad Fisa, Zul Aizat; Minhat, Halimatus Sakdiah; Mohd Zulkefli, Nor Afiah; Ahmad, Norliza (Public Library of Science, 2022)
Introduction: Men who have sex with men (MSM) living with HIV are more likely to be depressed than MSM without HIV. The AIDS epidemic will not end if the needs of people living with HIV and the determinants of health are not being addressed. Compared to HIV individuals without depression, depressed HIV individuals have worse clinical outcomes and higher mortality risk. Depression is caused by a complex combination of social, psychological, and biological variables. This systematic review, thereby motivated by the need to address this gap in the literature, aims to articulate determinants of depression among MSM living with HIV according to the biopsychosocial approach. Methodology;We systematically searched four databases from 2011 to 2021. We searched for observational studies on determinants of depression among MSM living with HIV. The outcome is depression based on the categorical or numerical outcome. Two reviewers independently extracted data and assessed study risks of bias. Any disagreements are consulted with the third reviewer. Results: We identified 533 articles, of which only eight studies are included. A total of 3,172 MSMs are included in the studies. We found the determinants of depression and categorized them according to biological, psychological, and social approaches. Conclusion: The determinants of depression with the strongest evidence across studies were enacted HIV-related stigma, unemployment, sleep disturbance, current smoker, black ethnicity, born overseas, ART initiation, and access to mental health care. Despite weaker evidence, the other relevant determinants to be included were older age, internalized stigma, self-efficacy, and social support. Efforts to improve or prevent depression among MSM living with HIV could benefit from addressing the determinants of depression based on the biopsychosocial approach immediately after HIV diagnosis. Integrating mental health screening and care into HIV treatment settings would strengthen HIV prevention and care outcomes and improve access to mental healthcare.